1977
DOI: 10.1002/chin.197743364
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: TUMOR INHIBITORS. 122. THE MAYTANSINOIDS. ISOLATION, STRUCTURAL ELUCIDATION, N, AND CHEMICAL INTERRELATION OF NOVEL ANSA MACROLIDES

Abstract: Ansamacrolide, z.B. (Ia), sowie Maytanbutacin (Ib) werden ‐ isoliert und ihre Strukturen bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…2 (AMT-815-20 g) was homogenized and extracted with CHCl 3 -MeOH (2:1) to give after evaporation a brown gum (1.2 g). The gum was subjected to partition by the method of Kupchan et al 9 For better separation, the carbon tetrachloride fraction (280 mg) was methylated with freshly destilled diazomethane and chromatographed on a Sephadex LH-20 column, eluting with a mixture of heptane-CHCl 3 -MeOH (2:1:1) to obtain compound 10 (9.5 mg 0.047%). A fraction of the latter column was subjected to VLC over silica gel, using heptane with increasing proportions of ethyl acetate as eluent.…”
Section: Extraction and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (AMT-815-20 g) was homogenized and extracted with CHCl 3 -MeOH (2:1) to give after evaporation a brown gum (1.2 g). The gum was subjected to partition by the method of Kupchan et al 9 For better separation, the carbon tetrachloride fraction (280 mg) was methylated with freshly destilled diazomethane and chromatographed on a Sephadex LH-20 column, eluting with a mixture of heptane-CHCl 3 -MeOH (2:1:1) to obtain compound 10 (9.5 mg 0.047%). A fraction of the latter column was subjected to VLC over silica gel, using heptane with increasing proportions of ethyl acetate as eluent.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…1 (AMT-839-17 g) was homogenized and extracted with CHCl 3 -MeOH (2:1) to give after evaporation a brown gum (0.92 g). The gum was subjected to partition by the method of Kupchan et al 9 The carbon tetrachloride fraction (320 mg) was repeatedly chromatographed on a Sephadex LH-20 column, eluting with acetone. Then it was subjected to vacuum-liquid chromatography (VLC) over silica gel, using heptane with increasing proportions of acetone as eluent.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…Cancer is a leading cause of death worldwide, hence intensive research focuses on finding effective and patient-friendly ways (e.g., new potent cytotoxic molecules, [1][2][3] the encapsulation of chemotherapeutically used drugs, 4 or photodynamic therapy 5 ) to treat the different types of cancers. Generally, drug delivery systems are used to enhance the specificity and selectivity of these therapeutic approaches for tumour cells, where small organic compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The mass spectrum was typical of a maytanside ester with peaks at m/e 616 corresponding to M+-H20-HNC0,2 mje 471 resulting from subsequent loss of the sidechain ester at C-3, m/e 456 due to loss of a methyl group from the m/e 471 ion, and mje 436 due to loss of a chlorine from the mje 471 ion. The pattern of ions at mje 471, 456, and 436 was typical of a maytansinoid with a demethyl C-l amide such as normaysine, and indicated that 2 had the same macrocyclic ring system as normaysine 3 (1). The loss of 145 mass units from mje 616 to m/e 471 suggested that the C-3 side chain ester was the same as in maytansine I, an ester of A'-acetyl-A'-methyl-L-alanine (1).…”
mentioning
confidence: 99%